Modeling Urban Air Quality: Impact of Spatial Wind Variation and Constant Removal on Pollution Dispersion in Delhi - Naveen; Sapna Ratan Shah (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
The dispersion of atmospheric pollutants is critically influenced by wind velocity and pollutant removal mechanisms. This study develops a comprehensive mathematical model to analyze pollution dispersion incorporating a distance-dependent wind profile and a constant rate of pollutant removal. A mixed-methods approach—combining analytical solutions, numerical simulation, and empirical validation—enables robust insights into the behavior of pollutant concentration over spatial domains. Simulation results tailored for Delhi reveal that PM2.5 concentrations decrease sharply from 180 µg/m³ at the emission source to 15.6 µg/m³ within 5 km, with over 60% reduction occurring within the first 2 km. The model demonstrates the compounded effect of increasing wind speed and removal rates, underscoring the significance of microclimatic gradients in pollutant dispersion. These findings offer critical implications for urban planning, buffer zone design, and environmental policy frameworks aimed at mitigating air pollution in megacities like Delhi.